Relationship between the Steuart resistance index of the umbilical artery in non-pathologic pregnancy and the weight and ponderal index of the newborn. - Clode, N (1992)
Umbilical artery Doppler velocimetry was performed at 28-32 and 36-38 weeks of gestation in a low risk population to correlate the Stuart's resistance index (Sistole/Diastole--S/D) to the weight and ponderal index of the newborn, and to determine the preditive value of S/D ratio greater than the 95 centil in the screening of newborns of weight or ponderal index lower than the 10 centil. Two hundred and eight two pregnant women were studied (146 at 28-32 weeks; 221 at 36-38 weeks) and Stuart Resistance Index was obtained by a continuous wave Doppler System. In both periods we had an inversely proportional correlation between the resistance index and the weight and ponderal index of the newborn; nevertheless the low sensibility and preditive value of the test shows that it should not be used as an isolated diagnostic tool to screen a low risk population for newborns with a low weight or low ponderal index.